Ánthropos peripateî: los argumentos del tercer hombre megáricos - Gardella, Mariana (2016)
The Platonic Theory of Forms has received many critiques from many critics, among which stands out the well-known «third man argument». Although traditionally the studies about this subject only have considered the versions of the argument introduced by Plato and Aristotle, the Megarian philosophers also developed other versions of the same reasoning. In this paper I would like to analyze the argument which is attributed by Alexander of Aphrodisias to «the sophists» and to Polyxenus in his commentary on Aristotle´s Metaphysics. I will try to show that the main point of these objections is to criticize the homonymy of the universal terms, a problem that Plato evokes in his Parmenides, where he also points out some difficulties in relation to the semantics of his own theory.